Comparing User Perceptions of Surgical Environments: Simulations in a High-Fidelity Physical Mock-Up Versus a Postoccupancy Evaluation. (April 2022) - Joseph, Anjali; Mihandoust, Sahar; Wingler, Deborah; Machry, Herminia; Allison, David; Reeves, Scott T.
Objective: The purpose of this study was to compare perceptions and behaviors of end users participating in simulations in a high-fidelity physical mock-up of an operating room (OR) prototype with the perceptions and behaviors of end users in the built out ORs postoccupancy. Background: Simulation-based evaluations of high-fidelity physical mock-ups of proposed layouts are increasingly being conducted during the facility design process to understand impacts on workflow and potential adverse patient safety outcomes. Nevertheless, it is unclear to what extent user experiences in these simulated healthcare spaces are similar to those in built and occupied healthcare environments. Methods: Using interviews, surveys, and observations, this study compared user evaluations in a high-fidelity physical mock-up of an OR with user evaluations of the built and occupied OR postoccupancy. Workflow disruptions were also analyzed using video recordings for a simulated pediatric surgery and five pediatric surgeries in the actual OR. Results: This study found that user perceptions and behavior in the two types of environments were mostly similar with regard to perceived support for the location of surgeon workstation, perceived space and task performance, perceived access to storage locations, boom setup, and OR cleanability. Participant's ratings differed for supportiveness of the mobile Circulating Nurse (CN) workstation, maneuvering booms, and environmental disruptions. Conclusion: Simulation-based evaluations are extremely beneficial during the design process and can provide valuable input to design teams as well as clinical teams about workflow and safety issues that allow design issues to be addressed before construction.